Рога в изобилии: повесть / Галина Куликова - Куликова Галина Михайловна (Шоу-детектив, 2003)
Экземпляры: АБ/1, ПФ/2 (20110124) / Инвентарный номер: 1 / Цена: 35.00 / Авт.знак: К 90 / ББК: 84(2Рос-Рус)6